LOGISTICS METHODS FOR MANAGING THE TRANSPORTATION OF HUMANITARIAN CARGO NEAR THE WAR ZONE - Muzykin, M. I.; Nesterenko, H. I.; Bibik, S. I.; Чубенко, О. І. (Systems and Technologies, 2025)
This article analyzes existing logistics systems, identifies problematic aspects of their functioning, and develops practical recommendations for optimizing the transportation of humanitarian cargo. The logistical delivery of humanitarian cargo faces many challenges near the war zone. The authors research the impact of various factors, including security risks for carriers, limited access to transport and infrastructure, adverse weather conditions, and insufficient coordination between different humanitarian organizations and local authorities. The characteristics of cargoes provided to citizens as humanitarian aid are considered, and a means of transport for transporting goods from large warehouses to intermediate storage facilities is selected, and transport routes are developed, taking into account the uncertainty of route selection due to shelling. Simulating the routes for delivering humanitarian aid to frontline settlements has been carried out. The research emphasizes that efficient transportation of humanitarian cargo from central warehouses to frontline areas is a complex but solvable challenge. Transporting cargoes from central warehouses to intermediate ones, developing routes for further transportation to humanitarian aid distribution points, and optimising the transport fleet are the main stages in developing an effective transport and logistics system. Specialised algorithms of linear programming tasks were used to allocate vehicles and minimise costs. In the event of a danger associated with hostilities, the availability of developed alternative routes ensures continuity of supply. Risk probability analysis makes it possible to choose the safest routes.